Cadmium (Cd) Contamination Status in Cisanti Lake (West Java, Indonesia) Analysis on Water, Sediment, and Bioaccumulation in Invasive Mussels Sinanodonta pacifica (Heude, 1878) - Manuel, David Reivaldo; Sahidin, Asep; Hasan, Zahidah; Herawati, Heti; Baihaqi, Faqih; Arief, Mochamad Candra Wirawan (Bogor Agricultural University, Indonesia, 2025)
Cisanti Lake, the strategic zero point of the Citarum River, faces the threat of cadmium (Cd) pollution from surrounding agricultural activities. Conducted during the dry season of 2024, this pioneering study assesses the Cd pollution status using a multicompartment approach (water, sediment, and bioindicator organism Sinanodonta pacifica, Heude 1878). Samples from the three stations were analyzed using Atomic Absorption Spectrophotometry (AAS). The concentration of Cd in water was very low (0.0012–0.0030 mg/L), but it accumulated significantly in sediment (0.37–0.65 mg/kg) and mussel tissue (0.20–0.30 mg/kg). Although the concentration in water and biota was below quality standards, ecological risk analysis revealed that the sediment has moderate contamination (Contamination Factor: 1.25–2.15) and acts as a long-term pollutant sink. S. pacifica proved effective in accumulating Cd from the water column, demonstrated by a high Bioconcentration Factor from water to biota (BCF b-w >75), making it a reliable bioindicator of Cd pollution. This study provides crucial baseline data on environmental management in the upstream Citarum and establishes sediment monitoring as a vital early warning tool for future pollution risks.